Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1038/modpathol.2013.229
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of ZEB1 by miR-200 characterizes Helicobacter pylori-positive gastric diffuse large B-cell lymphoma with a less aggressive behavior

Abstract: Primary gastric diffuse large B-cell lymphomas may or may not have a concurrent component of mucosaassociated lymphoid tissue lymphoma. Diffuse large B-cell lymphoma/mucosa-associated lymphoid tissue lymphomas are often associated with Helicobacter pylori (H. pylori) infection, suggesting that the large cells are transformed from mucosa-associated lymphoid tissue lymphomas. In contrast, only limited data are available on the clinical and molecular features of pure gastric diffuse large B-cell lymphomas. In 102… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 30 publications
(35 reference statements)
2
17
0
Order By: Relevance
“…Also, dysregulation of FOXD3 promotes gastric carcinogenesis [222]. Many other genes found upregulated by H. pylori are associated with cell cycle progression and proliferation (p14, p16, p21, p27, RAB40C, COX 2, FOS, ERBB2, FGFR2, ABL1, ECOP, JAK2, MYC, MET, SIRT1, PDCD4, TRAF6, GMNN, and CCNE2) [213, 223242], apoptosis (RECK, SMAD4, TRAIL, MCL1, BIM, XIAP, and PDK1) [243250], and invasion and metastasis (PTEN, WNT 5a, EDNRA, ROR2, EPB41L3, MMP1, MMP10, HMGA2, ROBO1, TGF- β , EZH2, casein kinase 2, and ZEB) [251262]. Several studies showed that the upregulation of inflammatory cytokines IL1- β , NOS 2, and TNF- α induced methylation [4649, 51, 52, 263].…”
Section: Methylationmentioning
confidence: 99%
“…Also, dysregulation of FOXD3 promotes gastric carcinogenesis [222]. Many other genes found upregulated by H. pylori are associated with cell cycle progression and proliferation (p14, p16, p21, p27, RAB40C, COX 2, FOS, ERBB2, FGFR2, ABL1, ECOP, JAK2, MYC, MET, SIRT1, PDCD4, TRAF6, GMNN, and CCNE2) [213, 223242], apoptosis (RECK, SMAD4, TRAIL, MCL1, BIM, XIAP, and PDK1) [243250], and invasion and metastasis (PTEN, WNT 5a, EDNRA, ROR2, EPB41L3, MMP1, MMP10, HMGA2, ROBO1, TGF- β , EZH2, casein kinase 2, and ZEB) [251262]. Several studies showed that the upregulation of inflammatory cytokines IL1- β , NOS 2, and TNF- α induced methylation [4649, 51, 52, 263].…”
Section: Methylationmentioning
confidence: 99%
“…Interestingly, miR200b miRNAs have been almost exclusively associated with solid tumours. A recent study suggests that the elevated miR200b expression and subsequent inhibition of zinc finger E-box-binding homeobox 1 transcription factor and increased BCL6 protein expression is associated with the better prognosis of the Helicobacter pylori -positive gastric diffuse large B cell lymphomas compared with H. pylori -negative ones 26. To this end, it would be interesting to investigate whether miR200b-5p levels are downregulated in other lymphomas that are not associated with SS.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, Zeb1 is almost absent in quiescent B cells of the mantle zone but it is expressed in proliferating GC B cells of tonsils (http://www.proteinatlas.org/ENSG00000148516-ZEB1/tissue/tonsil). High Zeb1 expression was also associated with adverse overall survival in diffuse large and mantle B cell lymphomas [4547]. The higher Zeb1 expression levels in malignant lymphomas suggest its involvement during B cell differentiation either at early stages or after BCR activation.…”
Section: Discussionmentioning
confidence: 99%